The Cemetery and Digital Collective Memory - Stefania Rasile (ARQ)
The means of storing and transmitting information are transforming funerary architecture and our relationship with death. Burial sites, which reflect social and religious hierarchies, have historically structured collective memory. Today, digital technologies —supported by new media— offer detailed archives for perpetual remembrance. Human and artificial intelligence are reshaping the construction and organization of memory in response to the technological possibilities of our era. Yet, this shift presents a paradox: the more we can remember —or, more precisely, digitally retrieve— the easier it becomes to forget. As digital storage expands, the paradox deepens, and what should remain accessible risks being lost in a sea of boundless, transient data.